Kepemimpinan Kepala Sekolah Pada Sekolah Berwawasan Islam - Muhammad Najib; Aslamiah Aslamiah; Asniwati Asniwati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the leadership of principals in schools with an Islamic perspective. This research applies a descriptive qualitative approach with a multisite study that includes several stages. Data was obtained from various sources, including school principals, teachers, and employees. Data collection techniques involve interviews, observation, and documentation. Data analysis was carried out interactively, including data reduction, presentation, and concluding. The validity of the data was tested through triangulation of sources and methods. Findings from the research show that school principals need to adopt leadership styles and strategies appropriate to the field's needs, situations, and conditions. This style and strategy aims to meet the needs of the school's leaders, hoping to create a harmonious and conducive situation. In conclusion, leadership styles and techniques can potentially increase collaboration between leaders, teachers, and employees in a conducive atmosphere. Sim Keywords: Style, leadership strategies, and effective schools